Integrating Blockchain Technology into Zakat Operational Systems: A Framework for Sharia-Compliant Transparency - Sabilsyah Nur Rachman; Faizi Faizi; Isma Addi Jumbri (Universitas Islam Sultan Agung, 2026)
Purpose - Zakat serves an essential function in advancing socio-economic welfare and mitigating poverty in Indonesia. Nonetheless, the actual collection of zakat is considerably below its estimated potential. The efficiency of zakat management is frequently hindered by structural challenges, particularly those pertaining to transparency, accountability, and the comparatively low level of public trust in zakat management institutions. This study aims to address these challenges by delineating and formulating a conceptual framework for the integration of blockchain technology into a sharia-compliant zakat operational system that is also congruent with Indonesia's financial regulations.Methodology/approach - To achieve this objective, the research adopts a qualitative approach within an interpretive paradigm. Data are collected through a systematic literature review of academic publications, government regulatory documents, and classical and contemporary Islamic jurisprudence (fiqh) literature. The collected data are then analysed using thematic analysis in order to construct a comprehensive governance model architecture.Findings – The findings propose an operational model comprising four integrated schemes: collection, allocation, reporting, and governance. Within this model, blockchain functions exclusively as a decentralised digital ledger for recording transaction trails, while the flow of funds continues to rely on fiat currency (Indonesian Rupiah). Additionally, smart contracts are implemented to automate allocation mechanisms with precision, thereby enhancing efficiency and reducing the likelihood of human error. From the perspective of Islamic commercial jurisprudence (fiqh muʿāmalah), this framework inherently fulfils the principle of record-keeping (al-kitābah) to ensure justice. It also automates the execution of agency contracts (wakālah) and serves as a preventive measure blocking the means (sadd al-dharīʿah) against the misappropriation of funds (ghulūw), without violating the prohibition of excessive uncertainty in contracts (gharâr). Overall, this study contributes to the Islamic fintech literature by offering a technology-based zakat governance model that strengthens accountability without replacing conventional banking infrastructure.Conclusion - Consequently, it is recommended that policymakers and zakat institutions adopt transparency mechanisms based on distributed ledger technology to mitigate operational risks, optimise fund collection, and sustainably restore public trust through appropriate and context-sensitive innovations.